Preparation process of high-elasticity acrylic fiber

Through the spinning process of acetate fiber and polyacrylonitrile, combined with the treatment of antibacterial liquid and flame retardant, a high-elastic acrylic fiber is formed, which solves the problem of insufficient elasticity and flame retardant performance of existing antibacterial acrylic fibers and significantly improves the fibers Flame retardant properties and antibacterial durability.

CN119162818AInactive Publication Date: 2024-12-20YAN TAI YOU YI ZHI XIAN YOU XIAN GONG SI

Patent Information

Application Number
CN202411688364.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The elastic properties and flame retardant effects of existing antibacterial acrylic fibers are insufficient, resulting in easy damage during use and inability to heat resistance during combustion.

Method used

Acetic fiber and polyacrylonitrile are stirred in dimethyl sulfoxide to form a spinning solution. After spinning, molding, washing, oiling, drying and curling, it is soaked in antibacterial liquid, coated with flame retardant and silica sol , and finally impregnate and dry in the hydrophobic liquid to form highly elastic acrylic fibers.

Benefits of technology

Through the synergistic effect of the composite flame retardant of sodium alginate and ammonium polyphosphate and silica sol, the flame retardant performance and thermal stability of the fiber are improved. The synergistic effect of the antibacterial components of silver nitrate and glucose is extended, which significantly improves the antibacterial effect. The mechanical properties and antibacterial durability of fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162818A_ABST
    Figure CN119162818A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process of high-elasticity acrylic fibers, and relates to the technical field of acrylic fibers, the preparation process comprises the following steps: uniformly mixing dried cellulose acetate fibers with polyacrylonitrile, pouring into dimethyl sulfoxide, heating and stirring, spinning to obtain nascent acrylic fibers, and carrying out double-diffusion molding, washing, oiling, drying and curling on the nascent acrylic fibers to obtain the high-elasticity acrylic fibers. The preparation method comprises the following steps: preparing acrylic fibers, soaking the acrylic fibers in an antibacterial solution, drying, coating a flame retardant, drying, curing in silica sol, and finally soaking in a hydrophobic solution to obtain the high-elasticity acrylic fibers. According to the preparation process of the high-elasticity acrylic fiber, ammonium polyphosphate and sodium alginate are compounded to serve as a flame retardant, so that in the combustion process of the fiber, sodium alginate is subjected to thermal decomposition, and a compact carbon layer is formed on the surface of the fiber, so that contact between oxygen and the fiber is blocked, and the flame-retardant effect is achieved; meanwhile, sodium alginate can form a three-dimensional network structure in the fiber, so that the heat resistance of the fiber during combustion is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acrylic fibers, in particular to a preparation process of high-elastic acrylic fibers. Background Art

[0002] The Chinese patent application with publication number CN110565204A discloses a composite antibacterial acrylic fiber. The invention adopts yeast fermentation, and loofah is added in the process. The plant fiber and bacterial fiber treated by enzymatic hydrolysis and fermentation degradation cooperate with each other to form a fiber adsorption film. The unfavorable factors can be combined with negative ions to be adsorbed by the mixed fiber membrane with good adsorption performance, providing a stable antibacterial effect; methyl methacrylate, acrylic acid, etc. are used as monomers for prepolymerization to form an emulsion with film-forming properties, and then adipic acid dihydrazide is added to form a stable emulsion, and the hydrophilic group produces internal crosslinking on the molecular structure to improve the water resistance stability; casein is used as a raw material for modification in the additive, which can better combine the macromolecular water-resistant components and the mixed fiber components, strengthen the water resistance and the retention of the antibacterial components. The invention solves the problem that the water resistance of the currently commonly used antibacterial acrylic fiber is poor, and the antibacterial components therein are easy to fall off during washing, resulting in a weakened antibacterial effect. However, the elastic properties and flame retardant effect of the acrylic fiber prepared above are insufficient, and need to be further improved; for this reason, the present invention provides a preparation process of high elastic acrylic fiber to solve the above problems. Summary of the invention

[0003] In view of the deficiencies of the prior art, the present invention provides a preparation process of high-elastic acrylic fiber, which solves the problems mentioned in the above background technology.

[0004] To achieve the above object, the present invention is implemented by the following technical scheme: A preparation process of high elastic acrylic fiber, comprising the following preparation steps: Step 1: Dry 30-50 g of cellulose acetate and 12-25 g of polyacrylonitrile in a 60-70°C forced air oven for 10-12 hours, and then in a 60-65°C vacuum oven for 30-36 hours; Step 2: Mix the dried cellulose acetate and polyacrylonitrile and pour into 65-80 mL of dimethyl sulfoxide, heat the oil bath to 55-65° C., stir at 200-300 rpm for 10-15 min, heat to 85-90° C., stir at 600-900 rpm for 50-65 min, and obtain a spinning solution; Step 3, spinning the spinning solution to obtain primary acrylic fiber; Step 4, double diffusion molding, washing, oiling, drying and curling the nascent acrylic fiber to obtain the acrylic fiber; Step 5: Soak 1-1.5 g of acrylic fiber in 95-100 mL of antibacterial solution, heat the water bath to 50-55° C., soak for 30-40 min, wash with deionized water 4-6 times, and then dry in a drying oven at 60-65° C. Step 6: coating the treated acrylic fiber surface with a flame retardant, and then drying the treated acrylic fiber in a drying oven; Step 7, immersing the acrylic fiber treated in step 6 in silica sol again, and then placing it in a drying oven, first heating it to 70-75°C for drying for 15-20 minutes, and then heating it to 110-120°C for curing for 5-8 minutes; Step 8: finally immerse the acrylic fiber treated in step 7 in the hydrophobic liquid for 7-10 hours, and then place it in a drying oven at 110-120° C. to dry it for 8-15 minutes, thereby obtaining high-elastic acrylic fiber.

[0005] Preferably, the preparation of the antibacterial liquid is: (1) 0.75-1.25 g of AgNO 3 Pour into 25-30 mL of deionized water, and after it is completely dissolved, add ammonia water dropwise while stirring until the solution changes from clear to turbid and then back to clear; (2) Add 25 g / L NaOH solution to adjust the pH value of the solution to 12-13, and then add ammonia water until the solution becomes clear to obtain solution A; (3) Pour 4-6.5 g of glucose and 1-2.4 g of tartaric acid into 100 mL of deionized water, heat to 95-100 °C, cook for 10-15 min, and then cool to room temperature; (4) After adding 10-15 mL of ethanol, add distilled water to obtain solution B; (5) Stir solution A and solution B to obtain an antibacterial solution.

[0006] Preferably, in (5), the volume ratio of solution A to solution B is 1:(2.5-3.5).

[0007] Preferably, in step 6, the flame retardant is prepared by pouring 0.5-0.7 g of ammonium polyphosphate into 1-3 g of sodium alginate aqueous solution and stirring for 15-20 min; and the coating amount of the flame retardant is 0.05-0.06 g / cm 2 .

[0008] Preferably, in step seven, the preparation method of silica sol is: at room temperature, 35-50 mL of ethanol and 1.5-3 mL of concentrated ammonia water are mixed and stirred for 25-30 min, and then 2-3 mL of ethyl orthosilicate is added dropwise, and stirring is continued for 1.8-2 h.

[0009] Preferably, in step eight, the hydrophobic liquid is a hexadecyltrimethoxysilane ethanol solution with a concentration of 7%. The method further includes pre-treating the hydrophobic liquid by stirring the hexadecyltrimethoxysilane ethanol solution for 30-35 minutes at room temperature.

[0010] Preferably, the preparation process of the high-elastic acrylic fiber also includes pretreating the acrylic fiber obtained in step four, specifically: placing the acrylic fiber in a 0.5 mol / L NaOH solution, heating it to 85-90°C for 35-40 minutes, then washing it with deionized water until the pH value of the washing liquid is 7, and then drying it in a drying oven.

[0011] Preferably, in step seven, the dipping-drying-curing operation is repeated 3-4 times.

[0012] The present invention provides a preparation process of high-elastic acrylic fiber. Compared with the prior art, it has the following beneficial effects: (1) The present invention uses ammonium polyphosphate and sodium alginate as a flame retardant, so that during the combustion of the fiber, the sodium alginate undergoes thermal decomposition to form a dense carbon layer on its surface, thereby blocking the contact between oxygen and the fiber and playing a flame retardant role. At the same time, the sodium alginate can form a three-dimensional network structure in the fiber, thereby improving the heat resistance of the fiber during combustion; and the ammonium polyphosphate decomposes when heated, which can promote the dehydration and carbonization of organic matter on the fiber surface, forming a carbon layer covering the fiber surface, isolating air and heat. At the same time, the ammonium polyphosphate will release non-combustible gases such as nitrogen when heated, diluting the oxygen concentration around the fiber. The flame retardant properties of the fiber are further improved. The silica sol and the hydrophobic liquid rely on the silicon element to enhance the strength of the carbon layer, improve the thermal stability of the fiber, and slow down the decomposition of the system. In summary, the synergistic effect of the mixture of ammonium polyphosphate and sodium alginate can synergistically exert a flame retardant effect in the fiber through multiple action mechanisms such as forming a carbon layer, dehydration carbonization, gas dilution, and heat insulation, thereby improving the flame retardant properties of the fiber. And sodium alginate, as a film-forming substance, can share the tensile force exerted on the fiber during the stretching process, which can not only improve the flame retardant properties of the fiber, but also significantly improve the mechanical properties of the fiber.

[0013] (2) The present invention uses silver nitrate as the main antibacterial component. Silver ions combine with bacterial proteins to destroy the bacterial cell structure and interfere with its physiological metabolic process, causing the bacteria to die. Tartaric acid is used to create an acidic environment to inhibit bacterial reproduction. At the same time, glucose is used as a reducing agent to promote the reduction of anions, thereby better contacting with bacteria and enhancing the antibacterial effect. At the same time, the synergistic effect of silver nitrate, tartaric acid and glucose is conducive to the slow release of antibacterial components such as silver ions, making the antibacterial effect more lasting, thereby extending the antibacterial time of the fiber. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a SEM picture of the acrylic fiber provided by the present invention before and after being treated with an antibacterial liquid. DETAILED DESCRIPTION

[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] In the technical solution, the vinyl content in the vinyl methyl siloxane is 15%. Example 1

[0017] A preparation process of high elastic acrylic fiber, comprising the following preparation steps: Step 1: Dry 30 g of cellulose acetate and 12 g of polyacrylonitrile in a 60° C. forced air oven for 10 h, and then in a 60° C. vacuum oven for 30 h; Step 2: Mix the dried cellulose acetate and polyacrylonitrile and pour into 65 mL of dimethyl sulfoxide, heat the oil bath to 55° C., stir at 200 rpm for 10 min, heat to 85° C., stir at 600 rpm for 50 min, and obtain a spinning solution; Step 3, spinning the spinning solution to obtain primary acrylic fiber; Step 4: double diffusion forming, washing, oiling, drying and curling the nascent acrylic fiber to obtain the acrylic fiber; firstly placing the acrylic fiber in a 0.5 mol / L NaOH solution, heating it to 85° C. for 35 min, then washing it with deionized water until the pH value of the washing solution is 7, and then drying it in a drying oven; Step 5: Soak 1 g of acrylic fiber in 95 mL of antibacterial solution and heat the water bath to 50° C. for 30 min, wash with deionized water 4 times, and then dry in a drying oven at 60° C. The preparation method of the antibacterial solution is as follows: 0.75 g of AgNO 3 Pour into 25 mL of deionized water, wait for complete dissolution, add ammonia water dropwise while stirring until the solution changes from clear to turbid and then to clear, add 25 g / L NaOH solution dropwise, adjust the pH value of the solution to 12, and then add ammonia water dropwise until the solution becomes clear to obtain solution A; pour 4 g of glucose and 1 g of tartaric acid into 100 mL of deionized water, heat to 95 ° C, boil for 10 min, cool to room temperature, add 10 mL of ethanol, and then add distilled water to obtain solution B; stir and mix solution A and solution B in a volume ratio of 1:2.5 to obtain an antibacterial solution; Step 6: Add flame retardant at 0.05g / cm 2 The coating amount is applied on the surface of the treated acrylic fiber, and then placed in a drying oven for drying; The flame retardant is prepared by adding 0.5 g of ammonium polyphosphate to 1 g of sodium alginate aqueous solution and stirring for 15 min. Step 7, the acrylic fiber treated in step 6 is immersed in silica sol again, and then placed in a drying oven, first heated to 70° C. for drying for 15 minutes, then heated to 110° C. for curing for 5 minutes, and the dipping-drying-curing operation is repeated 3 times; The preparation method of silica sol is as follows: at room temperature, 35 mL of ethanol and 1.5 mL of concentrated ammonia water are mixed and stirred for 25 minutes, and then 2 mL of ethyl orthosilicate is added dropwise, and stirring is continued for 1.8 hours to obtain the silica sol; Step 8: Under room temperature, stir a 7% hexadecyltrimethoxysilane ethanol solution for 30 minutes, then soak the fiber treated in step 7 in the hexadecyltrimethoxysilane ethanol solution for 7 hours, and then dry it in a drying oven at 110° C. for 8 minutes to obtain a high-elastic acrylic fiber. Example 2

[0018] A preparation process of high elastic acrylic fiber, comprising the following preparation steps: Step 1: Dry 40 g of cellulose acetate and 20 g of polyacrylonitrile in a 65° C. forced air oven for 11 h, and then in a 63° C. vacuum oven for 33 h; Step 2: Mix the dried cellulose acetate and polyacrylonitrile and pour into 70 mL of dimethyl sulfoxide, heat the oil bath to 60° C., stir at 250 rpm for 12 min, heat to 88° C., stir at 750 rpm for 60 min, and obtain a spinning solution; Step 3, spinning the spinning solution to obtain primary acrylic fiber; Step 4: double diffusion forming, washing, oiling, drying and curling the nascent acrylic fiber to obtain the acrylic fiber; firstly placing the acrylic fiber in a 0.5 mol / L NaOH solution, heating it to 87° C. for 38 min, then washing it with deionized water until the pH value of the washing solution is 7, and then drying it in a drying oven; Step 5: Soak 1.2 g of acrylic fiber in 96 mL of antibacterial solution and heat the water bath to 53° C. for 35 min, wash with deionized water 5 times, and then dry in a drying oven at 64° C. The preparation method of the antibacterial solution is as follows: 1.0 g of AgNO 3Pour into 28 mL of deionized water, wait for complete dissolution, add ammonia water dropwise while stirring until the solution changes from clear to turbid and then to clear, add 25 g / L NaOH solution dropwise, adjust the pH value of the solution to 13, and then add ammonia water dropwise until the solution becomes clear to obtain solution A; pour 5.5 g of glucose and 1.7 g of tartaric acid into 100 mL of deionized water, heat to 98 ° C, boil for 12 min, cool to room temperature, add 13 mL of ethanol, and then add distilled water to obtain solution B; stir and mix solution A and solution B in a volume ratio of 1:3 to obtain an antibacterial solution; Step 6: Add flame retardant at 0.05g / cm 2 The coating amount is applied on the surface of the treated acrylic fiber, and then placed in a drying oven for drying; The flame retardant is prepared by adding 0.6 g of ammonium polyphosphate into 2 g of sodium alginate aqueous solution and stirring for 18 min. Step 7, the acrylic fiber treated in step 6 is immersed in silica sol again, and then placed in a drying oven, first heated to 73° C. for drying for 16 minutes, then heated to 115° C. for curing for 7 minutes, and the dipping-drying-curing operation is repeated 4 times; The preparation method of silica sol is as follows: at room temperature, 45 mL of ethanol and 2.5 mL of concentrated ammonia water are mixed and stirred for 30 minutes, and then 2.5 mL of ethyl orthosilicate is added dropwise, and stirring is continued for 1.9 hours to obtain the silica sol; Step 8: Under room temperature, stir a 7% hexadecyltrimethoxysilane ethanol solution for 35 minutes, then soak the fiber treated in step 7 in the hexadecyltrimethoxysilane ethanol solution for 8 hours, and then dry it in a drying oven at 115°C for 10 minutes to obtain a high-elastic acrylic fiber. Example 3

[0019] A preparation process of high elastic acrylic fiber, comprising the following preparation steps: Step 1: Dry 50 g of cellulose acetate and 25 g of polyacrylonitrile in a 70° C. forced air oven for 12 h, and then in a 65° C. vacuum oven for 36 h; Step 2: Mix the dried cellulose acetate and polyacrylonitrile and pour into 80 mL of dimethyl sulfoxide, heat the oil bath to 65° C., stir at 300 rpm for 15 min, heat to 90° C., stir at 900 rpm for 65 min, and obtain a spinning solution; Step 3, spinning the spinning solution to obtain primary acrylic fiber; Step 4: double diffusion forming, washing, oiling, drying and curling the nascent acrylic fiber to obtain the acrylic fiber; firstly placing the acrylic fiber in a 0.5 mol / L NaOH solution, heating it to 90° C. for 40 min, then washing it with deionized water until the pH value of the washing solution is 7, and then drying it in a drying oven; Step 5: Soak 1.5 g of acrylic fiber in 100 mL of antibacterial solution and heat the water bath to 55° C. for 40 min, wash with deionized water 6 times, and then dry in a drying oven at 65° C. The preparation method of the antibacterial solution is as follows: 1.25 g of AgNO 3 Pour into 30 mL of deionized water, wait for complete dissolution, add ammonia water dropwise while stirring until the solution changes from clear to turbid and then to clear, add 25 g / L NaOH solution dropwise, adjust the pH value of the solution to 13, and then add ammonia water dropwise until the solution becomes clear to obtain solution A; pour 6.5 g of glucose and 2.4 g of tartaric acid into 100 mL of deionized water, heat to 100 ° C, boil for 15 min, cool to room temperature, add 15 mL of ethanol, and then add distilled water to obtain solution B; stir and mix solution A and solution B in a volume ratio of 1:3.5 to obtain an antibacterial solution; Step 6: Add flame retardant at 0.06g / cm 2 The coating amount is applied on the surface of the treated acrylic fiber, and then placed in a drying oven for drying; The flame retardant is prepared by adding 0.7 g of ammonium polyphosphate to 3 g of sodium alginate aqueous solution and stirring for 20 min. Step 7, the acrylic fiber treated in step 6 is immersed in silica sol again, and then placed in a drying oven, first heated to 75° C. for drying for 20 minutes, then heated to 120° C. for curing for 8 minutes, and the dipping-drying-curing operation is repeated 4 times; The preparation method of silica sol is as follows: at room temperature, 50 mL of ethanol and 3 mL of concentrated ammonia water are mixed and stirred for 30 minutes, and then 3 mL of ethyl orthosilicate is added dropwise, and stirring is continued for 2 hours to obtain the silica sol; Step 8: Under room temperature, stir a 7% hexadecyltrimethoxysilane ethanol solution for 35 minutes, then soak the fiber treated in step 7 in the hexadecyltrimethoxysilane ethanol solution for 10 hours, and then place it in a drying oven at 120° C. and dry it for 15 minutes to obtain a high-elastic acrylic fiber.

[0020] Comparative Example 1 Compared with Example 1, the flame retardant in Example 1 is replaced by ammonium polyphosphate.

[0021] Comparative Example 2 Compared with Example 1, the antibacterial liquid in Example 1 was replaced with AgNO 3 Solution.

[0022] Comparative Example 3 Compared with Example 1, the step of soaking the acrylic fiber in the silica sol and the hydrophobic liquid in Example 1 is deleted.

[0023] The fiber raw materials were placed under standard temperature and humidity (temperature 20°C, humidity 65%) for pre-humidification and humidity conditioning to achieve moisture absorption equilibrium, and the tensile properties of the fiber raw materials were tested.

[0024] Tensile properties: tested in accordance with GB / T14337-2008; the results are shown in Table 1.

[0025] Limiting oxygen index: tested in accordance with GB / T5455-1997; the results are shown in Table 1.

[0026] Elastic properties: The elastic recovery rate of the fiber was tested at 100% stretch using an XN-1 spandex elastic tester. The pre-tension was 0.01+0.001 cN / dtex, the stretching speed was 500 mm / min, and the tensile test distance was 50 mm. The results are shown in Table 1.

[0027] Antibacterial rate test: The test was carried out in accordance with GB / T20944.3-2008; the results are shown in Table 1.

[0028] Table 1

[0029] Abrasion resistance test: The test was conducted in accordance with GB3920-1997, and the test results were rated with reference to the gray scale for staining in GB251-1995 to evaluate the durability of the fiber after washing; the results are shown in Table 2.

[0030] Table 2

[0031] It can be seen from Table 2 that the dry friction fastness of the samples of Examples 1-3 can reach about level 4, and the wet friction fastness is also between levels 3-4, indicating that the surface silver-plated layer has strong bonding force, is not easy to peel or fall off, and has good stability. After 30 standard water washings, the dry and wet friction fastness of the samples only decreased by about half a level, indicating that the bonding force between the silver particles and the fiber surface is strong, and has certain stability and durability.

[0032] like Figure 1 As shown in the figure, the surface of the acrylic fiber before antibacterial liquid treatment is smooth with shallow grooves; after antibacterial liquid treatment, the surface of the acrylic fiber becomes rougher, which is due to the adsorption of elemental silver on the surface of the acrylic fiber.

[0033] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0034] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0035] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing high elastic acrylic fiber, characterized in that: The method comprises the following preparation steps: Step 1: Dry 30-50 g of cellulose acetate and 12-25 g of polyacrylonitrile in a 60-70°C forced air oven for 10-12 hours, and then in a 60-65°C vacuum oven for 30-36 hours; Step 2: Mix the dried cellulose acetate and polyacrylonitrile and pour into 65-80 mL of dimethyl sulfoxide, heat the oil bath to 55-65° C., stir at 200-300 rpm for 10-15 min, heat to 85-90° C., stir at 600-900 rpm for 50-65 min, and obtain a spinning solution; Step 3, spinning the spinning solution to obtain primary acrylic fiber; Step 4, double diffusion molding, washing, oiling, drying and curling the nascent acrylic fiber to obtain the acrylic fiber; Step 5: Soak 1-1.5 g of acrylic fiber in 95-100 mL of antibacterial solution, heat the water bath to 50-55° C., soak for 30-40 min, wash with deionized water 4-6 times, and then dry in a drying oven at 60-65° C. Step 6: coating the treated acrylic fiber surface with a flame retardant, and then drying the treated acrylic fiber in a drying oven; Step 7, immersing the acrylic fiber treated in step 6 in silica sol again, and then placing it in a drying oven, first heating it to 70-75°C for drying for 15-20 minutes, and then heating it to 110-120°C for curing for 5-8 minutes; Step 8: finally immerse the acrylic fiber treated in step 7 in the hydrophobic liquid for 7-10 hours, and then place it in a drying oven at 110-120° C. to dry it for 8-15 minutes, thereby obtaining high-elastic acrylic fiber.

2. The process for preparing a high elastic acrylic fiber according to claim 1, characterized in that: Preparation of the antibacterial solution: (1) Pour 0.75-1.25 g of AgNO3 into 25-30 mL of deionized water. After it is completely dissolved, add ammonia water dropwise while stirring until the solution changes from clear to turbid and then back to clear. (2) Add 25 g / L NaOH solution to adjust the pH value of the solution to 12-13, and then add ammonia water until the solution becomes clear to obtain solution A; (3) Pour 4-6.5 g of glucose and 1-2.4 g of tartaric acid into 100 mL of deionized water, heat to 95-100 °C, cook for 10-15 min, and then cool to room temperature; (4) After adding 10-15 mL of ethanol, add distilled water to obtain solution B; (5) Stir solution A and solution B to obtain an antibacterial solution.

3. The process for preparing a high elastic acrylic fiber according to claim 2, characterized in that: In the above (5), the volume ratio of solution A to solution B is 1:(2.5-3.5).

4. The process for preparing a high elastic acrylic fiber according to claim 1, characterized in that: In step 6, the flame retardant is prepared by pouring 0.5-0.7 g of ammonium polyphosphate into 1-3 g of sodium alginate aqueous solution and stirring for 15-20 min; and the coating amount of the flame retardant is 0.05-0.06 g / cm 2 .

5. The process for preparing a high elastic acrylic fiber according to claim 1, characterized in that: In step seven, the preparation method of silica sol is as follows: at room temperature, 35-50 mL of ethanol and 1.5-3 mL of concentrated ammonia water are mixed and stirred for 25-30 min, and then 2-3 mL of ethyl orthosilicate is added dropwise, and stirring is continued for 1.8-2 h.

6. The process for preparing a high elastic acrylic fiber according to claim 1, characterized in that: In the step eight, the hydrophobic liquid is a hexadecyltrimethoxysilane ethanol solution with a concentration of 7%. The step also includes pretreatment of the hydrophobic liquid: stirring the hexadecyltrimethoxysilane ethanol solution for 30-35 minutes at room temperature.

7. The process for preparing a high elastic acrylic fiber according to claim 3, characterized in that: The preparation process of the high-elastic acrylic fiber also includes pre-treating the acrylic fiber obtained in step 4, specifically: first placing the acrylic fiber in a 0.5 mol / L NaOH solution, heating it to 85-90° C. for 35-40 min, then washing it with deionized water until the pH value of the washing solution is 7, and then drying it in a drying oven.

8. The process for preparing a high elastic acrylic fiber according to claim 1, characterized in that: In the step seven, the dipping-drying-curing operation is repeated 3-4 times.

Citation Information

Patent Citations

  • Acetate fiber and preparation method thereof

    CN105002592A

  • Preparation method for antibacterial acrylic fiber

    CN105970614A

  • Preparation method of superhydrophobic antibacterial fabric

    CN108385375A

  • Antibacterial non-woven fabric

    CN111411513A

  • Preparation method of bio-based flame-retardant super-hydrophobic textile material

    CN115094630A

Cited By

  • Preparation method and application of seaweed modified acrylic fiber

    CN122485077A